2010
DOI: 10.1080/15459624.2010.483984
|View full text |Cite
|
Sign up to set email alerts
|

Permeation of Gasoline, Diesel, Bioethanol (E85), and Biodiesel (B20) Fuels Through Six Glove Materials

Abstract: Biofuels and conventional fuels differ in terms of their evaporation rates, permeation rates, and exhaust emissions, which can alter exposures of workers, especially those in the fuel refining and distribution industries. This study investigated the permeation of biofuels (bioethanol 85%, biodiesel 20%) and conventional petroleum fuels (gasoline and diesel) through gloves used in occupational settings (neoprene, nitrile, and Viton) and laboratories (latex, nitrile, and vinyl), as well as a standard reference m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…In contrast, acetone molecules accomplished this in just 60 hours (2.5 days), notably quicker than toluene molecules. In a study examining gasoline, diesel, bioethanol, and biodiesel permeation [ 26 ], the composition of permeated vapors showed enrichment in components with high vapor pressure. This observation suggests that chemicals possessing high vapor pressure evaporate more rapidly from materials.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, acetone molecules accomplished this in just 60 hours (2.5 days), notably quicker than toluene molecules. In a study examining gasoline, diesel, bioethanol, and biodiesel permeation [ 26 ], the composition of permeated vapors showed enrichment in components with high vapor pressure. This observation suggests that chemicals possessing high vapor pressure evaporate more rapidly from materials.…”
Section: Discussionmentioning
confidence: 99%
“…This way, although uniforms function as a barrier, fuels may penetrate the materials used for manufacturing them. A study performed by Chin & Batterman 30 investigated the permeation of biofuels and petroleum-based fuels, including gasoline and diesel fuel, through fabrics used in chemical protective clothing. Permeation tests were performed for 4 types of fuel (regular gasoline, ethanol + gasoline, diesel fuel, and biodiesel) through 3 types of gloves commonly used as chemical protective equipment and 3 types of gloves used in laboratory environments.…”
Section: Methodsmentioning
confidence: 99%
“…Among all analyzed samples, gasoline presented the highest rate of permeation through the tested materials. 30 …”
Section: Methodsmentioning
confidence: 99%
“…While aviation fuel was not explicitly tested, many of the fuels contained similar volatile chemicals to those found in jet and synthetic jet fuels, namely, benzene and toluene. The specific study found that volatile compounds in blended fuels still penetrated glove material at rates similar to those of neat fuels . Therefore, the presence of volatile organic compounds rather than the total content of volatiles affects permeation rates for PPE, and it was recommended that both neat and blended fuels should have the same gloving requirements.…”
Section: Risk Controlsmentioning
confidence: 99%
“…Barrier creams and emollients can provide additional protection to that of PPE, but their use must follow the education of workers on the amount (at least 1 g per hand) and frequency (every three to four hours) required for increased effectiveness . Moreover, permeation rates for different combinations of automobile fuels were examined . While aviation fuel was not explicitly tested, many of the fuels contained similar volatile chemicals to those found in jet and synthetic jet fuels, namely, benzene and toluene.…”
Section: Risk Controlsmentioning
confidence: 99%